DEWA BULAN DALAM MASYARAKAT JAWA KUNA, SEBAGAI LATAR CERITA ANAK MASA KINI - T N Hari Lelono (Balai Arkeologi Kalimantan Selatan, 2008)
Many people in many nations have long perceived the moon as an inspirational element in establishing stories, tales or myths for children in forms of poems, poetries, rhymes or proverbs. In daily life, children and adults usually have tete-a-tete and a leisure entertainment of games under the full moon. In regard to religious aspect, some societies recognize the moon as a symbol of fertility. In Indonesian, the moon also plays an important a spiritual role. What is the concept in the Hindu-Buddhist culture on perceiving the moon, especially in Java during the 4th until the 14th century. However, archaeological evidences indicate the lack of attention and need to create statues of the moon god, Candra. Apparently, the visualization of the moon appears merely as a crescent moon places behind of a god’s head. This article discusses the identity of Candra in regard to his mythological background, image and the comparison between Indonesian perceptions to that of the Indians.